Endogenous versus exogenous growth factor regulation of articular chondrocytes. Issue 1 (14th September 2013) - Shi, Shuiliang; Chan, Albert G.; Mercer, Scott; Eckert, George J.; Trippel, Stephen B.
ABSTRACT Anabolic growth factors that regulate the function of articular chondrocytes are candidates for articular cartilage repair. Such factors may be delivered by pharmacotherapy in the form of exogenous proteins, or by gene therapy as endogenous proteins. It is unknown whether delivery method influences growth factor effectiveness in regulating articular chondrocyte reparative functions. We treated adult bovine articular chondrocytes with exogenous recombinant insulin‐like growth factor‐I (IGF‐I) and transforming growth factor‐beta1 (TGF‐β1), or with the genes encoding these growth factors for endogenous production. Treatment effects were measured as change in chondrocyte DNA content, glycosaminoglycan production, and aggrecan gene expression. We found that IGF‐I stimulated chondrocyte biosynthesis similarly when delivered by either exogenous or endogenous means. In contrast, exogenous TGF‐β1 stimulated these reparative functions, while endogenous TGF‐β1 had little effect. Endogenous TGF‐β1 became more bioactive following activation of the transgene protein product. These data indicate that effective mechanisms of growth factor delivery for articular cartilage repair may differ for different growth factors. In the case of IGF‐I, gene therapy or protein therapy appear to be viable options. In contrast, TGF‐β1 gene therapy may be constrained by a limited ability of chondrocytes to convert latent complexes to an active form. Published 2013 by Wiley Periodicals, Inc. on behalf of the Orthopaedic Research Society. J Orthop Res 32:54–60, 2014.